Future perspectives on urban afforestation in relation to planting design : learning from three paradigmatic cases - Jensen, Rasmus Bartholdy (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2007)
Afforestation, as part of remedying the vast exploits of the forest resource in NW Europe, seems to have a high importance on both EU and national level. Due to the fact that this part of Europe is densely populated it is fair to say that a major part of afforestation will be situated within urban influences and is hence future urban forest. Social and Recreational aspects are usually of higher importance than economic aspects in an urban area. Looking at one important aspect of recreation is visual aspects. Four different visual criteria has been identified (scale, diversity, naturalness and visual accessibility) together with three management criteria (flexibility, knowledge and resources) which all represents essential sides to afforestation design. In order to relate the criteria to an analysis of different afforestation designs, profile diagrams were used. These profiles were developed as a "snapshot" from 10 years through 25, 50, 90 and some older. Using profile diagrams as a tool made it easy to make a comparative study of three afforestation paradigms - Classical forestry, Nature Based forestry and the Landscape laboratory approach. By using "high, medium and low" as value in relation to each criteria a comprehensive matrix was made. The analysis made it evident that designing together with proper management gives a wide palette of visual aspects. When relating to different surveys of forest types and public interests it is clear that the interests are very wide. In a design perspective this gives motivation to keep variation high to accommodate a wide range of users and to keep a flexible system.